Ação dos revestimentos em multicamadas intercaladas de carragenana (Hypnea musciformis) e quitosana (Ucides cordatus) no shelf life em filés de atum (Thunnus albacares) refrigerado - Vale, Diego Alves do (2023)
The commitment to search for a new edible coating technique for food is a constantly researched strategy, with the aim of improving its quality. The construction of intercalated multilayer coatings is a method that uses the electrostatic attraction of oppositely charged functional groups, carrageenan and chitosan have these charges, which makes their use feasible, in addition, the different antimicrobial and antioxidant properties add the biological potential in coatings. The objective of the present research was to analyze the antimicrobial and antioxidant properties, with different concentrations of carrageenan and chitosan, in the elaboration of interspersed multilayer coatings of carrageenan and chitosan in the conservation of tuna fillets (Thunnus albacares) refrigerated at 1°C±0.3 through physical-chemical and microbiological analyzes. In the antioxidant analysis, chitosan showed a significant difference (p>0.5) than carrageenan within the evaluated formulations, being more efficient for DPPH radical scavenging capacity, ferrous ions chelating activity (FIC) and ferric reducing antioxidant power (FRAP), however, for β-carotene bleaching (BCP) carrageenan was more efficient than chitosan. The intercalated multilayer coating of 0.6% (m/v) showed a significant difference (p>0.5) when compared to the 0.2% concentration (m/v), for nitrogen of total volatile bases (N-BVT), nitrogen of trimethylamine (N-TMA), thiobarbituric acid reactive substances (TBARS). Samples coated with 0.6% (w/v) showed the lowest counts of psychrotrophic bacteria, in addition to a bactericidal or bacteriostatic effect for histamine-producing bacteria up to the fifth day, with lower values in subsequent counts. The 0.6% (m/v) interlayer multilayer coating can be used to increase the shelf life of refrigerated tuna up to the fifteenth day, however, the 0.2% (m/v) concentration can be used even with a lower quality, since the values are within the limits allowed by Brazilian legislation.